2019
DOI: 10.1002/ps.5369
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic pyrethroid resistance ofAedes albopictus, with focus on the 2017 chikungunya outbreak in Italy

Abstract: BACKGROUND The highly invasive mosquito species Aedes albopictus has become a major health concern in temperate areas due to its role as vector of exotic arboviruses. Pyrethroid insecticides represent the main tools for limiting the circulation of such mosquito‐borne viruses. The present work aim to extend previous reports on phenotypic pyrethroid‐resistance in European Ae. albopictus, to identify its genetic basis and to monitor the geographical distribution of resistant genotypes, with a particular focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 58 publications
4
53
0
1
Order By: Relevance
“…However, the effectiveness of these interventions is limited, mostly because of the inherent difficulty in targeting all potential larval sites, as well as a lack of coordinated/synchronized implementation in public and private areas, insufficient resources and poor community participation. Therefore, in several highly infested areas, pyrethroid‐based insecticide space‐spraying is extensively carried out by public administrations and private citizens to reduce adult biting and associated nuisance, despite little evidence of long‐term effectiveness and increasing risk of the development of insecticide resistance . Notably, although pyrethroids are considered relatively safe for humans (EU Directive 528/2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effectiveness of these interventions is limited, mostly because of the inherent difficulty in targeting all potential larval sites, as well as a lack of coordinated/synchronized implementation in public and private areas, insufficient resources and poor community participation. Therefore, in several highly infested areas, pyrethroid‐based insecticide space‐spraying is extensively carried out by public administrations and private citizens to reduce adult biting and associated nuisance, despite little evidence of long‐term effectiveness and increasing risk of the development of insecticide resistance . Notably, although pyrethroids are considered relatively safe for humans (EU Directive 528/2012.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in several highly infested areas, pyrethroid-based insecticide space-spraying is extensively carried out by public administrations and private citizens to reduce adult biting and associated nuisance, despite little evidence of long-term effectiveness 14,15 and increasing risk of the development of insecticide resistance. [16][17][18] Notably, although pyrethroids are considered relatively safe for humans (EU Directive 528/2012. Biocidal Products Regulation 528/2012), they represent environmental contaminants toxic to non-target insect species, such as aquatic invertebrates and fishes.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded 1534C allele frequencies raised above 40% in populations from southern and central Greece, peaking in Attica (68.3%). Previous studies also reported relatively high mutation frequencies (reaching 66%) in populations sampled from the Attica region [47,48]. To date, kdr F1534C has also been recorded in Brazil [49], Singapore, Vietnam [50] and China [51], while other substitutions in the same genomic locus, F1534L and F1534S, also associated with pyrethroid resistance, have been identified in the USA, China, Vietnam and Italy [47,[50][51][52].…”
Section: Discussionmentioning
confidence: 78%
“…Genotyping of the VGSC gene for the detection of mutations associated with pyrethroid resistance revealed a widespread distribution of the kdr mutation F1534C across the country, following initial reports of the mutation in Greece [47,48]. The recorded 1534C allele frequencies raised above 40% in populations from southern and central Greece, peaking in Attica (68.3%).…”
Section: Discussionmentioning
confidence: 94%
“…albopictus have been recorded in Ae. albopictus populations from Italy and Greece where the mutation 1534C was detected at a frequency of 24.2% in the Athens population [19,20].…”
Section: Introductionmentioning
confidence: 99%